2019
DOI: 10.1521/pedi_2018_32_368
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Memory Impairment in Borderline Personality Disorder: A Quantitative Meta-Analysis Interpreted in Terms of the CaR-FA-X Model

Abstract: Borderline personality disorder (BPD) is characterized by impaired functioning of autobiographical memory (AM). We use a quantitative meta-analysis to assess AM performance in adults diagnosed with BPD as compared to healthy controls (HC). Moderator variables included type of autobiographical memory as well as clinical and demographic variables. Large significant deficits were seen in the BPD group in comparison to the HC group. In the BPD group, effect sizes were large for overgenerality, omission, and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…These studies were first summarized in the work of Williams et al (2007). Subsequent quantitative and qualitative reviews have been conducted in specific populations with discrete psychiatric presentations (Berna et al, 2016; Beran et al, 2019; Liu et al, 2013; Ono et al, 2015). However, no study has yet meta-analyzed the entire literature regarding autobiographical memory specificity/overgenerality across all studies that compare people with psychiatric diagnoses to diagnoses-free people.…”
mentioning
confidence: 99%
“…These studies were first summarized in the work of Williams et al (2007). Subsequent quantitative and qualitative reviews have been conducted in specific populations with discrete psychiatric presentations (Berna et al, 2016; Beran et al, 2019; Liu et al, 2013; Ono et al, 2015). However, no study has yet meta-analyzed the entire literature regarding autobiographical memory specificity/overgenerality across all studies that compare people with psychiatric diagnoses to diagnoses-free people.…”
mentioning
confidence: 99%
“…AM retrieval is altered in several mental disorders [15,17,18]. As discussed, patients with PTSD and BPD have better AM retrieval after hydrocortisone administration than healthy controls do [1,2], suggesting a normalization of AM performance.…”
Section: Introductionmentioning
confidence: 88%
“…Bech, Elkilit and Simonsen [20] in their systematic review reported no OGM in BPD when comorbid depression was controlled for. Beran, Richman and Unoka [23] on the other hand found a large effect size for OGM in BPD. One explanation for the diverging results could be that Beran et al [23] did not control for comorbid MDD.…”
Section: Introductionmentioning
confidence: 94%
“…Beran, Richman and Unoka [23] on the other hand found a large effect size for OGM in BPD. One explanation for the diverging results could be that Beran et al [23] did not control for comorbid MDD. One possible interpretation of the differences of retrieval style between patients with MDD and patients with BPD is provided by Conway and Pleydell-Pearce's model [24] about ABMs and the working self.…”
Section: Introductionmentioning
confidence: 94%